Bibliometric Analysis of Special Needs Education Keyword Using VOSviewer Indexed by Google Scholar - Dwi Novia Al Husaeni; Asep Bayu Dani Nandiyanto; Rina Maryanti (Universitas Pendidikan Indonesia (UPI), 2023)
Special needs education is a field of study that focuses on providing educational services to children with special needs who have learning and developmental challenges. The goal of this research is to combine mapping analysis with the VOSviewer app. The Publish or Perish application is used to find publications that are relevant to the keywords that have been entered. The term